Pesticide Toxicity Profile: Triazole Pesticides: PI-68/PI105, 9/2005 - Fishel, Frederick M. (EDIS, 2005)
This document provides a general overview of human toxicity, provides a listing of laboratory animal and wildlife toxicities and a cross reference of chemical, common and trade names of triazole pesticides registered for use in Florida. This document is PI-68, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 2005.